2019
DOI: 10.1007/s00701-019-03819-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between preoperative edema and postoperative cognitive functioning and health-related quality of life in WHO grade I meningioma patients

Abstract: Background Studies on the associations between preoperative cerebral edema, cognitive functioning, and health-related quality of life (HRQOL) in WHO grade I meningioma patients are virtually lacking. We studied the association between preoperative cerebral edema on postoperative cognitive functioning and HRQOL 6 months postoperatively in WHO grade I meningioma patients. Methods Twenty-one consecutive WHO grade I meningioma patients, who underwent surgery, were matched i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Cerebral blood flow and cerebral blood volume are also significantly low in the peritumoral edema [22]. Previous study has reported that the apathy is much severe in patients with brain edema of medial frontal meningioma [23], and preoperative cerebral edema in WHO grade I meningioma patients is correlated with post operative cognitive dysfunction [24]. In contrast, Tucha et al showed preoperative edema was not associated with cognitive function after surgery [25].…”
Section: Discussionmentioning
confidence: 95%
“…Cerebral blood flow and cerebral blood volume are also significantly low in the peritumoral edema [22]. Previous study has reported that the apathy is much severe in patients with brain edema of medial frontal meningioma [23], and preoperative cerebral edema in WHO grade I meningioma patients is correlated with post operative cognitive dysfunction [24]. In contrast, Tucha et al showed preoperative edema was not associated with cognitive function after surgery [25].…”
Section: Discussionmentioning
confidence: 95%
“…Table 1 summarizes the characteristics of all included studies and their corresponding patients that underwent neuropsychological cognitive evaluation prior to and after treatment. Overall, 9 retrospective [ 5 , 23 , 24 , 30 , 33 , 34 , 35 , 36 , 37 ] and 13 prospective [ 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 38 , 39 , 40 ] studies were reviewed, corresponding to a total of 1572 patients (range 9–261) with a mean age of 58.4 years (range 23–87). Most patients were female (n = 1084, 68.9%), with a female-to-male ratio of 2.3:1.…”
Section: Resultsmentioning
confidence: 99%
“…The identified literature consists of 18 cohorts treated with surgery [ 5 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 40 ], 3 cohorts that benefited from both surgery and adjuvant radiotherapy due to partial tumor removal [ 35 , 37 , 39 ], and 1 cohort that only received radiotherapy/radiosurgery [ 38 ] as a single treatment modality ( Table 2 and Supplementary Materials ). Table 2 provides a selected subset of the 5 biggest cohorts analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenesis of PTBE in meningiomas is highly variable and multifactorial 20,21 . The mechanisms operating in edema genesis have not been completely elucidated 22‐25 . The expression of vascular permeability factor/vascular endothelial growth factor (VPF/VEGF) and its endothelial receptor “flt‐1” has been studied in MM by Christov et al, who reported that the density of vessels positive for VPF/VEGF/flt‐1 expression was much higher with MM than in other solid meningiomas, possibly ascribing it as a key role as a driver for microcyst formation.…”
Section: Discussionmentioning
confidence: 99%